2021
DOI: 10.1007/s13365-020-00925-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronically elevated depressive symptoms interact with acute increases in inflammation to predict worse neurocognition among people with HIV

Abstract: We examined the joint effects of depressive symptoms (Beck Depression Inventory-II (BDI-II)) and systemic inflammation (plasma C-reactive protein (CRP)) on longitudinal profiles of neurocognition in a cohort of 143 people with HIV (PWH) on antiretroviral therapy. Global neurocognition, processing speed, motor skills, and attention/working memory all worsened as CRP increased but only among PWH who, on average, exhibited moderate to severe depressive symptoms (BDI-II > 22). Findings suggest that some PWH with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
2
10
0
3
Order By: Relevance
“…Our multivariable analyses of the TS cohort also confirmed that a level of depressive symptoms consistent with at least mild depression (BDI-II > 13), was also significantly associated with NC performance, supporting the contribution of depression to worse NC outcomes in PWH, which that has been recently reported in the CHARTER cohort 100; 101 . These results also implicate a potential interaction between the rs13045 A allele and depression, which is currently under investigation.…”
Section: Discussionsupporting
confidence: 86%
“…Our multivariable analyses of the TS cohort also confirmed that a level of depressive symptoms consistent with at least mild depression (BDI-II > 13), was also significantly associated with NC performance, supporting the contribution of depression to worse NC outcomes in PWH, which that has been recently reported in the CHARTER cohort 100; 101 . These results also implicate a potential interaction between the rs13045 A allele and depression, which is currently under investigation.…”
Section: Discussionsupporting
confidence: 86%
“…Future studies should also examine HIV-associated biotypes that could potentially modify the observed associations between cardiac IA and depressive symptom severity. Given that PWH treated with ARTs in advantaged countries are often able to achieve undetectable viral load status and CD4+ cell recovery, there has been a shift in attention to other HIV biotypes such as humoral and cellular inflammation status also shown to be predictive of HIV-associated mood disturbance and neurocognitive impairment (100)(101)(102)(103). Functional imaging studies reveal that both cognitive and interoceptive task performance and corresponding activity in mid-insula and anterior-insula do vary as a function of change in levels of peripheral inflammation (104,105).…”
Section: Discussionmentioning
confidence: 99%
“…This report is unique in evaluating the joint contributions of systemic inflammation and depression to long-term neurocognitive decline. Numerous reports link depression ( Watkins and Treisman, 2015 ; Namagga et al., 2021 ; Kohn et al., 2021 ) and both systemic and neuroinflammation ( Tedaldi et al., 2015 ; Hong and Banks, 2015 ; Gannon et al., 2011 ; Saloner et al., 2021 ) to neurocognitive impairment in HIV. Our work complements and extends these prior observations.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive reports have delineated the contributions of depression ( Pinheiro et al., 2016 ; Rubin and Maki, 2019 ), inflammation ( Alakkas et al., 2019 ; McGuire et al., 2015 ; Burdo et al., 2013 ) and neurodegeneration ( Mackiewicz et al., 2019 ; Wenzel et al., 2019 ; Pulliam et al., 2019 ; Bryant et al., 2015 ) separately to neurocognition. For example, we examined the joint effects of depression (Beck Depression Inventory-II; BDI-II) and systemic inflammation (plasma CRP) on longitudinal profiles of neurocognition over and average of 33 months of follow-up in 143 PWH on ART ( Saloner et al., 2020 ). Global cognition, processing speed, motor function, and attention/working memory all decreased as CRP increased, but only among PWH who exhibited moderate to severe depressive symptoms (BDI-II>22).…”
Section: Introductionmentioning
confidence: 99%